2017
DOI: 10.3389/fmars.2017.00304
|View full text |Cite
|
Sign up to set email alerts
|

The Northeast Greenland Shelf as a Potential Habitat for the Northeast Arctic Cod

Abstract: Observations (1978)(1979)(1980)(1981)(1982)(1983)(1984)(1985)(1986)(1987)(1988)(1989)(1990)(1991) of distributions of pelagic juvenile Northeast Arctic cod (Gadus morhua L.) show that up to 1/3 of the year class are dispersed off the continental shelf and into the deep Norwegian Sea while on the way from the spring-spawning areas along the Norwegian coast to the autumn-settlement areas in the Barents Sea. The fate of this variable fraction of pelagic juveniles off-shelf has been an open question ever since Joh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 50 publications
5
24
0
Order By: Relevance
“…DiscussionOur results show that the NE Greenland shelf is readily reached by cod, redfish and shrimp from the Barents Sea, probably advected across the Fram Strait by the Return Atlantic Current, supporting recent simulation studies[25][26][27] . Advection plays an important role in the northward transport of plankton in the Barents Sea, via the West Spitsbergen Current 18 and because up to 50% of this water is estimated to cross the Fram Strait[28][29][30] , the Return Atlantic Current provides a connection between the Barents Sea and the NE Greenland shelf ecosystems.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…DiscussionOur results show that the NE Greenland shelf is readily reached by cod, redfish and shrimp from the Barents Sea, probably advected across the Fram Strait by the Return Atlantic Current, supporting recent simulation studies[25][26][27] . Advection plays an important role in the northward transport of plankton in the Barents Sea, via the West Spitsbergen Current 18 and because up to 50% of this water is estimated to cross the Fram Strait[28][29][30] , the Return Atlantic Current provides a connection between the Barents Sea and the NE Greenland shelf ecosystems.…”
supporting
confidence: 85%
“…The NE Greenland shelf ecosystem is severely understudied and biodiversity baselines are fragmentary with no timeline 45 . It is therefore difficult to establish whether our findings reflect a recent shift driven by ocean warming or constitute a 27 demonstrates that between 2.4% and 12% of 0-group NEAC may be transported northwest along the proposed route ( Fig. 2a).…”
Section: Resultsmentioning
confidence: 94%
“…Instead, zooplankton in the Uncertain Fate region might remain in recirculating AW, and could also be transported westward toward Greenland . Model simulations have shown that episodic events can transport cod larvae hatched outside the Norwegian coast toward Northeast Greenland, by taking the route with AW northward toward Svalbard and then westward across Fram Strait (Strand et al, 2017). The high abundances of Calanus sp.…”
Section: Eddy Activity and Zooplankton Transportmentioning
confidence: 99%
“…We illustrate how a model accounting for only two traits, the asymptotic size and growth rate, can be used to systematically quantify the sensitivity of fish stocks to environmental variability and fishing pressure. Frequently, larval survival and, accordingly, recruitment success is directly or indirectly influenced by the environment through factors such as food availability [33], drifting to favourable nursery habitats [34,35] and the effect of temperature on growth [36]. However, species with an asymptotic weight of around 140 g and a growth rate of > 3 g 0.25 year −1 showed less than 20% variability (log 10 = −0.7) in their recruitment in the present simulation.…”
Section: Discussionmentioning
confidence: 63%